TECHNOLOGY MANAGEMENT FOR SUPPLY CHAIN IN SPORTS CLUBS IRAQI AND ITS REFLECTION ON THE EXCELLENCE PERFORMANCE - Al-Qaysi, Bilal .J; Atallah Hussein, Hafsa (International Journal of Supply Chain Management, 2019)
This research seeks to spread the culture of total quality management among employees at all levels of management in sports clubs working in Iraq and the duration of their reflection on the creation of outstanding performance, and to explore any of the variables of TQM more influential performance excellence studies aims: Identify the latest trends in total quality management and the requirements for applying them in sports clubs to raise their performance within the sports sector Design/methodology/approach: The descriptive descriptive approach was used. The questionnaire was used to collect data in order to develop a reliable and correct measurement model for TQM variables and their distances. The hypotheses were tested using some statistical treatments. Findings : The study concluded the sample agreement that the distinct performance is directly affected by TQM and its dimensions (administrative leadership, continuous improvement, process improvement, relationship marketing). The model of measurement of these variables has been developed. Moreover, the results support the hypothesis of influence and correlation between the investigated variables . Practical implications:This study provides a useful measure of overall quality management and performance, helping managers and employees at the sports club levels to assess the current status of club performance. Managers may improve their performance programs more effectively and efficiently through their strategic approaches to competition. Originality / value: This study is committed to assisting the administrations working in the sports sector to address the challenge of increasing the performance of sports clubs through the management of total quality and its dimensions.